UJI BEBERAPA ZAT PENGATUR TUMBUH ALAMI TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell Arg) STUM MATA TIDUR - Arif, Muhammad; ', Murniati; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rubber plant (Hevea brasiliensis Muell Arg) was one of important plantation commodity as second source of foreign exchange after palm oil. The main result of rubber tree is latex as raw material for manufacture of transport equipment, medical and household appliances. This study aimed to determine the effect of the use some natural plant growth regulators on the growth of budded stump and get the best of natural plant growth regulators for budded stump rubber plant. This research has been carried out in technical services unit of Agriculture Faculty, Riau University. This research was conducted with completely randomized design (CDR) consisting of 4 treatment namely : without giving PGR, giving coconut water, green bean extract, and young bamboo extract. Each treatment was repeated 4 times with each unit consisting of 3 seedling experiment and total number of seedling was prepare 48 seedling. The data were analyzed used analysis of variance (ANOVA) and continued by least significant difference (LSD) at 5%. The parameters measured were : buds appear time, shoot length, number of petiole, shoot diameter and leaf area. The result showed that provision of coconut water with 750 cc/l concentration showed the best growth of budded stump rubber plant at parameters buds appear time, shoot length, number of petiole and shoot diameter. Keyword : rubber plant, budded stump, plant growth regulators